Стратегічні напрями реалізації міжрегіонального співробітництва - Татарченко, О.М. (Культура народов Причерноморья, 2013)
Запропоновано структуру та логіку побудови стратегії міжрегіонального
співробітництва. Стратегію міжрегіонального співробітництва виражено через комплекс
довгострокових цілей, завдань і напрямів узгоджених дій регіональних і державних органів влади,
владних структур територій, що співробітничають, на досягнення головної мети – підвищення
добробуту населення регіону за допомогою використання його економіко-географічних переваг на основі
створення стійкої і збалансованої системи міжрегіональних і міждержавних взаємозв'язків. Стратегію
міжрегіонального співробітництва представлено як трирівневу систему, що включає стратегічну мету
та напрями розвитку, стратегічні дії міжрегіонального співробітництва. Обґрунтовано етапи оцінки
факторів розвитку міжрегіонального співробітництва. Предложена структура и логика построения стратегии межрегионального
сотрудничества. Стратегия межрегионального сотрудничества виражена посредством комплекса
долгосрочных целей, заданий и направлений согласованных действий региональных и государственных
органов власти, властных структур сотрудничающих территорий, направленных на достижение
главной цели – повышение благосостояния населения региона с помощью использования его экономико-
географических преимуществ на основе создания устойчивой и сбалансированной системы
межрегиональных и межгосударственных взаимосвязей. Стратегия межрегионального сотрудничества
представлена как трехуровневая система, включающая стратегическую цель и направления развития,
стратегические действия межрегионального сотрудничества. Обоснованы этапы оценки факторов
развития межрегионального сотрудничества. The structure and logic of construction of inter-regional collaboration strategy was introduced. The
strategy of inter-regional collaboration is represented as a system of long-term aims, tasks and directions ofcoordinated actions of regional and governmental authorities of co-operating territories, which are directed at
achievement of mien goal – the increase of prosperity of regional citizens with the help of usage of its economicgeographical
advantages on the basis of creation of stable and balanced system of inter-regional and inter-state
interrelations. The strategy of inter-regional collaboration is presented as a system, that consist of three levels,
strategic goal and development lines, strategic actions of inter-regional collaboration. The phases of es timation
of inter-regional collaboration development factors were grounded. The strategic directions of realization of
inter-regional collaboration are defined as the strategic measures (actions), which can supply the removal of
obstructive factors, achievement of goals of inter-regional collaboration development and realization of
governmental goals of state-partners. It was grounded, that the inter-regional collaboration is a mechanism,
which is able to have a positive influence on social-economic development of the region with the help of merging
of competitive advantages and inter-regional integration stimulation. The development of long-term documents
of social-economic development, as well as territorial planning schemes on different levels are considered as an
agreement mechanism of mutual interests of regions.